Lubrication Regimes in High-Performance Polymer Spur Gears. (16th January 2013) - Dearn, K. D.; Hoskins, T. J.; Andrei, L.; Walton, D.
Abstract : Little has been published on the behaviour of polymer gears operating under lubricated conditions. An experimental and analytical programme was undertaken to classify the regimes of EHL under which polymer spur gears operate. In doing so theoretical film thicknesses were calculated and then used to classify the regime according to Johnson's Map. The effects of lubrication on the operating efficiencies of high-performance polymer gears were interpreted and from these results coefficients of friction were derived. In addition to this the effect of tooth geometry was investigated and the beneficial influence of high-pressure angle tooth geometry is demonstrated. At loads typically associated with polymer gears the operating regime is shown to be mixed film lubrication. When high-pressure angle gears were tested at high loads the operating regime became full film lubrication and relatively little tooth flank damage occurred.